CSS floating - Meyer, Eric A. (O'Reilly Media, 2016)
While flowing text around images is certainly nothing new, with CSS you can float any element, from images to paragraphs to lists. In this practical guide, author Eric Meyer reveals some interestingu2014and surprisingu2014ways to use CSS floats in your web design, including the latest capability to flow content past non-rectangular float shapes. Short and sweet, this book is an excerpt from the upcoming fourth edition of CSS: The Definitive Guide. When you purchase either the print or the ebook edition of CSS Floating, youu2019ll receive a discount on the entire Definitive Guide once itu2019s released. Why wait? Learn how to bring life to your web pages now. Learn the characteristics of floated elements, and CSS rules for using them Be aware of certain rule exceptions when applying floats to your design, including the use of negative margins Use the clear property to prevent floats from affecting elements in the next section of the document Create floating boxes in non-rectangular shapes, including rounded corners, circles, ellipses, and even polygons Define float shapes with transparent or opaque images.